From person-oriented to person-centered psychology. Abstracting structures of relationships. - Jaan Valsiner (Journal for Person-Oriented Research, 2015)
Although the investigation of persons should be natural for psychological science by its inherent logic, this has not been the case in the history of the discipline, where selected other species – rats, dogs, pigeons, and chimpanzees – have been made to “stand in” for human beings. Consequently the knowledge of human psychological processes has been slow to advance, and recurrent calls for “bringing the person back” into psychology are needed. Moving beyond such calls, I distinguish the Person-Oriented and Person-Centered perspectives that both have had times of appearance, disappearance, and re-appearance in the history of psychology. In the search for new forms of person-centered research, unpacking the processes that remain hidden behind the generic term relationship makes it possible to advance consistently qualitative perspectives on human life course. These processes operate at the border of the person and environment, and in the quest for understanding what happens at that border Person-Oriented and Person-Centered approaches of today are complementary.